KOMUNIKASI TERAPEUTIK PERAWAT DENGAN TINGKAT KECEMASAN KELUARGA PASIEN DI RUANG INTENSIVE CARE UNIT - Rezki, Ismia Maulida; Lestari, Dhian Ririn; Setyowati, Anggi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2016)
Therapeutic communication is a base tool used for making correlation between nurse and patientfamily. Patient family feels that their interaction with nurse is oppurtunity to explain feel whichdisturb so need for anxiety solving. Aim of this research to analyze correlation therapeuticcommunication of nurse with patient family anxiety level. Method of This research observationalanalysis with total respondent were 30 patients family in Intensive Care Unit (ICU) GeneralHospital (RSUD) Ratu Zalecha Martapura between 28 November to 7 December 2015. Thisresearch instruments used Therapeutic Communication of Nursing questionnaire and HamiltonAnxiety Rating Scale (HARS) questionnaire. Results of this research is communication of nursegood were 83,4%, therapeutic comunication of nurse enough were 16,7. There were no anxiety33,3%, low anxiety were 33,4%, middle anxiety were 16,6%, high anxiety were 16,7%. Result ofcorelation spearman statistic p value= 0,000 and coefficient correlation spearman (r)= -0,816. pvalue 0,000<0,05. Communication therapeutic of nurse related with patient family anxiety level.Communication therapeutic of nurse can be used as nursing intervention by nurse to patientfamily in ICU.